Retrofitting Digestate Recirculation System to Improve Methane Yield in Anaerobic Digestion - Elang Nur Reiz M N Insaani; Hafif Dafiqurrohman; Adi Surjosatyo; Cindy Rianti Priadi; Baskoro Lokahita (Journal of World Science, 2026)
Digestate recirculation has gained attention as a promising strategy to enhance methane production. By reintroducing acclimatized microorganisms and residual biodegradable compounds into Anaerobic digestion (AD) system, this approach can potentially improve process stability and biogas quality. To systematically evaluate these effects, modeling and simulation offer a reliable framework for assessing methane yield. This study aims to assess the feasibility of simulating methane production from an anaerobic digestion reactor using food waste (FW) as the primary feedstock, incorporating a digestate recirculation system. It is hypothesized that recirculated digestate, due to its high organic content and catalytic properties, can effectively enhance biogas quality and optimize energy recovery from the system. A process flow diagram was developed in Aspen Plus® version, incorporating the four main biochemical stages: hydrolysis, acidogenesis, acetogenesis, and methanogenesis. The Non-Random Two-Liquid (NRTL) thermodynamic model was applied to represent polar mixture components, and a total of 46 governing equations were implemented to describe anaerobic digestion kinetics and mass balances. Model performance was validated against data reported in previous studies. Simulation results indicate that increasing the recirculation ratio up to 30% into feedstock mixture enhances both methane up to 25% higher compared to baseline and biogas production up to 32% higher than baseline. The findings demonstrate that the usage of recirculated digestate could improve the biogas quality. The developed modeling framework shows strong potential for scalability and can be applied to optimize methane production in anaerobic digestion systems with similar feedstock compositions and operating conditions.